2022
DOI: 10.1016/j.ijscr.2021.106750
|View full text |Cite
|
Sign up to set email alerts
|

Variations of intestinal malrotation in adults: A case report of midgut volvulus and literature review for the surgeon

Abstract: Introduction Intestinal malrotation is a rare congenital abnormality occurring in 0.2–1% of the population. Adult presentations comprise only 0.2–0.5% of all cases leading to diagnostic challenges and worse outcomes in adults. We present a rare case of chronic/intermittent midgut volvulus with unique anatomic findings in an adult with intestinal malrotation. Presentation of case An 18-year-old Caucasian male presented to a community hospital with abdominal pain, nausea,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…[11][12][13][14] On the contrary, in adult patients, clinical manifestations tend to be diverse and are often nonspecific, encompassing acute, chronic acute, chronic, and incidental symptoms. [3,[15][16][17] Adult congenital intestinal malrotation typically presents as intestinal obstruction, which is accompanied by malnutrition and intestinal necrosis in some cases. [18] A study has observed that only approximately 20% of the patients exhibit acute symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] On the contrary, in adult patients, clinical manifestations tend to be diverse and are often nonspecific, encompassing acute, chronic acute, chronic, and incidental symptoms. [3,[15][16][17] Adult congenital intestinal malrotation typically presents as intestinal obstruction, which is accompanied by malnutrition and intestinal necrosis in some cases. [18] A study has observed that only approximately 20% of the patients exhibit acute symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, rates of surgery for adult-diagnosed malrotation can be less than 15%, with few adult patients ultimately undergoing the recommended Ladd’s procedure for this pathology [ 15 ]. Delayed or missed diagnosis in the unexpected adult population can lead to increased morbidity and mortality, as well as inadequate or inappropriate cares [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the nonspecific symptoms, laboratory examinations, and the diagnosis of midgut malrotation mainly depend on plain abdominal radiography, upper gastrointestinal radiography, barium enema, computed tomography (CT), and MRI. [ 14 ] Conventional radiography is neither sensitive nor specific for malrotation, despite the possible suggestion of a right jejunal marker and colon without stool filling in the right lower abdomen. The barium meal series of the upper gastrointestinal tract remains accurate; that is, the duodenal jejunal junction does not cross the midline and lies below the level of the duodenal bulb.…”
Section: Discussionmentioning
confidence: 99%